2002
DOI: 10.1159/000063276
|View full text |Cite
|
Sign up to set email alerts
|

Moving from CFC Aerosol to HFA Aerosol or Dry Powder Inhalers: What Do Patients Think?

Abstract: Background/Objectives: Environmentally friendly hydrofluoroalkane (HFA) pressurised metered-dose inhalers are currently being marketed to replace chlorofluorocarbon (CFC)-driven devices. It is uncertain whether these new formulations with different properties are acceptable to patients. Similarly, switching a patient to a dry powder inhaler (DPI) carries the risk of non-acceptance. Methods: One hundred patients with obstructive airway disease on regular CFC aerosol inhaler medication underwent a standardised, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Moreover, because the drug is dissolved in the propellant, solutions can be tailored to extrafi ne drug delivery, reducing the particle size of emitted aerosol and thereby allowing deeper penetration in the bronchial tree. Switching from a CFC pMDI to an HFA pMDI was well accepted by most patients in one study (Hartung et al 2002): the taste was described as good and sweet, and the softer and slower jet was appreciated.…”
Section: Technical Aspects Of Inhaled Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, because the drug is dissolved in the propellant, solutions can be tailored to extrafi ne drug delivery, reducing the particle size of emitted aerosol and thereby allowing deeper penetration in the bronchial tree. Switching from a CFC pMDI to an HFA pMDI was well accepted by most patients in one study (Hartung et al 2002): the taste was described as good and sweet, and the softer and slower jet was appreciated.…”
Section: Technical Aspects Of Inhaled Therapymentioning
confidence: 98%
“…In recent decades, possible adverse effects on health and the environment as a result of the destruction of the earth's ozone layer by CFC paved the way for the ban of these compounds under the Montreal Protocol (Hartung et al 2002;Newman, 1990). New propellants without ozone-damaging properties -hydrofl uoroalkanes (HFA) -have been developed, and reformulated, environmentally friendly inhalers have been shown to be nontoxic, safe, and effective.…”
Section: Technical Aspects Of Inhaled Therapymentioning
confidence: 99%
“…This, combined with the possibility of fl ow resistance due to moisture within the device [13] , indicates that DPIs may not always be suitable alternatives to pMDIs. Further, consideration should be given to the risk of non-acceptance leading to non-compliance when patients are switched from pMDIs to DPIs as noted by Hartung et al [14] who found that not all powder devices were equally acceptable to patient These factors have led some experts to recommend that, during the transition from old inhalers to new, patients currently using a CFC pMDI should be switched to a CFC-free pMDI rather than a DPI, the latter only being considered if clinically indicated [13] . Modulite ® (Chiesi Farmaceutici S.p.A.) is a new type of pMDI that has been developed in response to the Montreal Protocol.…”
Section: Discussionmentioning
confidence: 99%
“…But these cumulative innovations have not been exclusively beneficial. The patenting of these novel drug administration methods has resulted in pharmaceutical companies regaining monopoly rights in the production of once common, and inexpensive, generic asthma drugs [103]. Such monopoly privileges restrict access and impose cost-barriers [104,105] to medications that many impoverished people require to live free of severe disability (elevated costs of treatment are also a major factor in patient non-compliance to therapy [106]).…”
Section: Methodsmentioning
confidence: 99%